2015
DOI: 10.1136/tobaccocontrol-2014-051661
|View full text |Cite
|
Sign up to set email alerts
|

Testing warning messages on smokers’ cigarette packages: a standardised protocol

Abstract: Purpose Lab experiments on cigarette warnings typically use a brief one-time exposure that is not paired with the cigarette packs smokers use every day, leaving open the question of how repeated warning exposure over several weeks may affect smokers. This proof of principle study sought to develop a new protocol for testing cigarette warnings that better reflects real-world exposure by presenting them on cigarette smokers’ own packs. Methods We tested a cigarette pack labeling protocol with 76 US smokers age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 41 publications
0
40
0
2
Order By: Relevance
“…Future studies are needed to test the effect of multiple exposures over a long period of time. Indeed, a recently published protocol establishes a methodology for testing real-word exposure to cigarette package warnings over time (Brewer et al, 2015), and a study in which smokers carried packages with graphic warnings for one week found that smokers paid more attention to graphic than to text-only warnings, and that five of the nine warnings were associated with greater thoughts of health risks (McQueen et al, 2015). Third, race/ethnicity groups included in this study were limited to white, African American, and Hispanic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are needed to test the effect of multiple exposures over a long period of time. Indeed, a recently published protocol establishes a methodology for testing real-word exposure to cigarette package warnings over time (Brewer et al, 2015), and a study in which smokers carried packages with graphic warnings for one week found that smokers paid more attention to graphic than to text-only warnings, and that five of the nine warnings were associated with greater thoughts of health risks (McQueen et al, 2015). Third, race/ethnicity groups included in this study were limited to white, African American, and Hispanic.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study focused on attitudes, just one predictor of subsequent behavior. Studies of the type described by Brewer et al (2015) that measure smoking behavior are needed to fully evaluate the effectiveness of graphic health warnings on cigarette packages. Even in countries where graphic health warnings have been in place, more data are needed to establish their utility in promoting smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of experimental studies of GWLs up to 201325 found only one study assessing behavioural outcomes,21 one study using multiple-exposure protocols26 and no studies that affixed warning labels onto participant cigarette packs. Recent studies address these limitations by using multiple exposure protocols and assessing behavioural outcomes,27 28 including quit attempts lasting for at least 1 day 26 29. Brewer et al 30 recently published an experimental study assessing the effect of GWLs on quit attempts during a 30-day exposure to GWLs placed on participant cigarette packs.…”
mentioning
confidence: 99%
“…Brewer et al 30 recently published an experimental study assessing the effect of GWLs on quit attempts during a 30-day exposure to GWLs placed on participant cigarette packs. However, the growing number of experimental studies that measured behavioural outcomes relied on self-report 26 30 31. The current paper reports on an experimental study using multiple exposures to GWLs on cigarette packs over 30 days, with a directly observed behavioural outcome (attending a smoking cessation group).…”
mentioning
confidence: 99%
“…In the protocol, smokers bring a supply of cigarette packs to weekly appointments; then, study staff label the cigarette packs while smokers take a survey [29]. In the current proof of principle study, we aimed to adapt the UNC protocol for evaluating warnings for e-cigarette devices and refills.…”
Section: Introductionmentioning
confidence: 99%